Aplikasi PhET sebagai Penunjang Media Pembelajaran Praktikum IPA Pada Kalangan Siswa Sekolah Menengah - Salmaan, Axel Faiz; Alfianto, Dede; Al-Musthafa, Hibban Mullah (Aktualisasi Pengabdian Masyarakat, 2023)
In early March 2020, WHO declared it a global pandemic because the world was being hit by the Covid-19 virus. The spread of this virus is very fast with a worldwide reach. Indonesia itself has entered two years of the Covid-19 pandemic since the first time the virus entered Indonesia. As a result of the pandemic, learning activities that started face-to-face at schools have experienced a transfer of the learning process to virtual or online learning. Along with this situation, the development of applications is also rapid, such as PhET which is an interactive learning media that can be used as a support for student practicum. PhET is an application that allows students to do practicum easily using a smartphone or PC. The method of review or literature study is made to summarize how PhET applications are applied in the world of education. Based on the articles and journals that have been cited, most PhETs are very helpful in making simple practicums at home so that it makes it easier for teachers to carry out practicums without having to face to face. However, several weaknesses were found in the application where students had to be guided by the teacher to do practicum. Therefore, teachers are required to try hard to explain the material that must be delivered so that students understand and understand how to use this PhET application. In addition, this learning can only be accessed via smartphones and PCs that are connected to the internet so that not all students can access it.